Analisis Komparatif Bahasa Jurnalistik dalam Program Berita Pagi di Stasiun TV Nasional Indonesia - Lapina Lena; Della Meira; Putri Handayani (Institut Nalanda, 2025)
This study analyzes the comparative use of journalistic language in two morning news programs on Indonesian national television: Selamat Pagi Indonesia on TVRI and Berita Pagi on RCTI. The research aims to explore the differences and similarities in the journalistic language employed by both programs, considering factors such as the institutional context and target audiences. By utilizing a literature review approach, this study examines how the two stations adapt their journalistic strategies to meet audience needs. The analysis reveals that while TVRI uses a more formal and educational language style, RCTI opts for a more flexible, dynamic approach. This comparative analysis highlights the role of journalistic language in shaping audience perception and enhancing program credibility.